The Beauty of Men Never Dies : An Autobiographical Novel - Leddick, David (Book collections on Project MUSE., 2013)
This melding of memoir and fiction recounts with humor and candid observation a gay man's romances in his seventies, offering insight into the joys (and a few of the sorrows) of loving, living, and aging with grace, style, and a fearless sense of fun. Bouncing between Montevideo, New York, and Paris, the narrator reveals his adventurous life, his many lovers, his varied careers from dancer to advertising, and the upbeat outlook that sustains him as he pursues the elusive Fenil, a handsome Uruguayan policeman.